Subject advantage in covert dependencies : the case of wh-questions comprehension in French Sign Language - Donati, Caterina; Hauser, Charlotte; Aristodemo, Valentina (Syntax (Oxford, England), 2022)
Studies on sentence processing have shown that, as with all A-bar dependencies, content questions involving wh movement display a subject advantage. Very little is known, however, about wh-in-situ questions. The aim of this article is to fill this gap and explore whether a subject advantage can be found in wh-in-situ questions. We report the results of a sentence-to-picture matching task using in-situ wh questions in French Sign Language. Three adult populations with different ages of exposure to sign language were studied. Results show that comprehension of wh-in-situ questions in French Sign Language does display a subject advantage. We argue that this is relevant for the analysis of wh in situ, supporting a covert-movement analysis against alternatives involving some form of (unselective) binding. Moreover, comparison of our three populations shows that delayed exposure to language has an impact on the comprehension of wh questions, confirming that early language deprivation affects language competence in adulthood.